Stock Market Resilience: Evaluating Islamic and Conventional Indices through COVID-19 Waves - Khursheed, Zamrud; Rehman, Moghis; Ahmad, Moeez; Ali, Ahmad (iRASD Journal of Economics, 2024)
The study examined the impact of the five COVID-19 waves on Pakistan's conventional (KSE-100) and Islamic (KMI-30) stock indices from March 3, 2020, to August 30, 2022. The DCC GARCH (1, 1) model found weak, predominantly negative connections between COVID-19 cases each day and stock returns. Visual data indicated a slight decrease in both indices as cases increased, reflecting previous findings on pandemics' adverse effects on stock markets. A thorough examination of the linkages between COVID-19 cases and financial indicators using Wavelet Coherence analysis highlighted intricate connections that are important to policymakers and financiers. Pakistan's KSE100 and KMI-30 indices showed a constant significant positive dynamic conditional association that persisted throughout the investigation. This challenges the perception that the Islamic index serves as a safe haven during financial crises. According to the research, Islamic stock markets, as reflected by the KMI-30, were not as protective or as good at hedging during crises like the COVID-19 pandemic. In fact, they were more susceptible to economic downturns. When navigating the effects of global health crises on financial markets, investors and policymakers must have a thorough understanding of these dynamics.